PEMETAAN DAERAH RAWAN KEBAKARAN DI LAHAN GAMBUT BERDASARKAN POLA SEKUENS TITIK PANAS DI KABUPATEN PULANG PISAU KALIMANTAN TENGAH - Anissa Rezainy; Lailan Syaufina; Imas Sukaesih Sitanggang (Graduate School Bogor Agricultural University (SPs IPB), 2020)
Land and forest fire is one of the major that caused Indonesia’s deforestation, who has a significant impact to the environment, loss of conservation, air pollution and economic loss. This research makes a spatial modelling along with factor that can affect collerates the forest fire. Spatial model of vulnerability of land and forest fire is built by composite mapping analysis method. Hotspot that is used in this research is the results of data mining processing, with sequential pattern mining technique which to find the relationships between the occurances of sequential event and pattern that often appear. From the six variables that influence land and forest fire there are four variables that impacts on the study area, that is forest zone, depth of peatland, distance of irrigation, and distance of road. The fire in the area of study occurs many times in the peatland area with the depth of 400-800 cm. Land and forest fire occurs frequently in 100-900 meters from irrigation and land and forest fire also occurs frequently in 1-4 km form the road. Land and forest fire occurs frequently in protected forest